Respuesta :

Answer:

x = approx. 1.24 or -7.24

Step-by-step explanation:

It's hard to factor directly so we should use the quadratic formula or complete the square. I'm going to go with completing the square.

x²+6x-9=0

x²+6x=9

x²+6x is the same as x²+2·3·x, in order to make this into the algebraic identity (A+B)²=A²+2AB+B², we must add B², or in this case 3² to both sides. (A is x, B is 3)

x²+6x+9=18

(x+3)²= 18

x+3= ±√18

x= ±4.24 -3 (approximately 4.24)

First solution for  x = 4.24-3 = 1.24

Second solution for x = -4.24-3 = -7.24




The roots or zeroes of the equation x² + 6x - 9 = 0 will be negative of (3 + 3√2) and negative 3 + 3√2.

What is a factorization?

It is a method for dividing a polynomial into pieces that will be multiplied together. At this moment, the polynomial's value will be zero.

The equation is given below.

x² + 6x - 9 = 0

Then the zeroes of the equation will be given by the formula method.

x² + 6x - 9 = 0

a = 1, b = 6, c = -9

Then we have

[tex]\rm x = \dfrac{-b \pm \sqrt{b^2 - 4ac }}{2a}\\\\x = \dfrac{-6 \pm \sqrt{6^2 - 4*1*(-9) }}{2*1}\\\\x = \dfrac{-6 \pm \sqrt{36 + 36 }}{2}\\\\x = \dfrac{-6 \pm \sqrt{2 * 36 }}{2}[/tex]

On further solving, we have

x = (- 6 ± 6√2) / 2

x = - 3 ± 3√2

x = -3 - 3√2, - 3 + 3√2

More about the factorization link is given below.

https://brainly.com/question/6810544

#SPJ2